PENGARUH LIKUIDITAS DAN PROFITABILITAS TERHADAP KEBIJAKAN DIVIDEN PADA PT CHAROEN POKPHAND INDONESIA TBK PERIODE 2012-2021 - Rifqi Radifan, Arya; Zulfitra (Journal of Research and Publication Innovation, 2024)
The purpose of this research is to determine Profitability and Liquidity of Dividend Policy at PT. Charoen Pokphand Indonesia. The method used is quantitative descriptive, namely conducting research on the problems faced by companies regarding their financial performance. The analytical data used is quantitative data, namely data in the form of company financial reports expressed in the form of numbers. Population and Sample. In this research, the population used is the Financial Report of PT. Charoen Pokphand Indonesia and the sample in this research is the Financial Report in the form of the Balance Sheet and Profit and Loss Report of PT. Charoen Pokphand Indonesia. in the period 2012 to 2021. Hypothesis testing obtained a t value of |0.432| < ttable 2.30600 then tcount < ttable and the significant value is 0.679 > 0.05. So it can be concluded that Ho1 is accepted and Ha1 is rejected, so it can be concluded that the Current Ratio has a negative and insignificant effect on the Dividend Payout Ratio. Hypothesis testing obtained a tcount value of 2.007 < ttable 2.30600, so the tcount and significant value were 0.085 > 0.05. It can be concluded that Ho2 is accepted and Ha2 is rejected, so it can be concluded that Return on Equity has a positive and insignificant effect on the Dividend Payout Ratio. Hypothesis testing obtained an Fcount value of 2.321 and Ftable of 4.459, which means Fcount < with Ftable 4.459 (2.321 < 4.459) with a significance level of 0.169 > 0.05, so H03 is accepted and Ha3 is rejected. Thus, this shows that the Current Ratio and Return on Equity simultaneously have a positive and insignificant effect on the Dividend Payout Ratio.